Isotopic evidence for temperature variation during the early Cretaceous (late Ryazanian–mid-Hauterivian) (2000)
Oxygen and carbon isotopic compositions have been determined from the belemnite genera Acroteuthis and Hibolites sampled from the early Cretaceous (Ryazanian–Hauterivian) interval of the Speeton Clay Formation, Filey Bay, England. The Speeton Clay Formation consists of a series of claystones and calcareous mudrocks deposited in an epicontinental sea. 18O values from belemnites, which met petrographic and chemical criteria for well preserved skeletal carbonate, indicate warm marine palaeotemperatures (c. 12–15°C) for much of the early Valanginian whilst cool temperatures (<9°C) are inferred for the earliest Hauterivian. During the remainder of the Hauterivian, temperatures fluctuated considerably and rose to a maximum of 15.5°C. Changes in kaolinite and smectite abundances, considered to reflect humid and arid phases of climate, correlate with warm and cool episodes. The palaeotemperature record, appears to contradict evidence from cephalopod faunas, which show a Tethyan influx during the inferred early Hauterivian cool period. However, this was a transgressive phase and thus the cephalopods could have been less sensitive to temperature than to water column stability and to land barriers. A positive shift in the carbon isotope profile obtained from the Speeton belemnites appears correlatable with carbon isotope profiles recorded from pelagic Tethyan successions, albeit with somewhat differing absolute values. The data support earlier models of carbon isotope variation, in that positive excursions are associated with an inferred global rise in sea level.